One Foot Raised: A Pilgrimage toward Sustainability - Cuyegkeng, Ma. Assunta C (Archīum Ateneo, 2020)
Speaker: Dr. Assunta C. Cuyegkeng The meaning of sustainability has evolved since the 70s. The role of the Ateneo Institute of Sustainability has been to translate this word into something concrete, such as university policy, research, degree programs, training and workshops. It has meant engaging stakeholders so that sustainability can be part of how we live and who we are. It has become a response to the call of Laudato Si’ to care for our common home with a holistic approach, from big systems to the personal and spiritual. The shared process of internalizing what it means to be sustainable has not always been easy but like a group of pilgrims plodding toward something sacred and bigger, it has become a journey of conversion for many. -- Dr. Assunta C. Cuyegkeng is a Professor at the Department of Leadership and Strategy of the John Gokongwei School of Management at the Ateneo de Manila University. She is also the Director of the Ateneo Institute of Sustainability, the Director of the ASEAN University Network on Ecological Education and Culture (AUN-EEC), and the Managing Editor of the Journal of Management for Global Sustainability. She obtained her PhD in Chemistry from the University of Regensburg in Germany, and her BS and MS degrees in Chemistry from Ateneo de Manila University. She has written on polymers, science education, environment, quality assurance, and leadership. Her literary essays, poems, and Filipino translations appear in various anthologies.